Modes of Knowledge acquisition and their reflections on the tacit knowledge A field study in Tuz General Hospital - السعيدي, يعرب عدنان; عبد القاسم, محمد قاسم (Journal of Economics and Administrative Sciences, 2016)
This research aims to knowledge the extent of the application of Tuz General Hospital to the concept of tacit knowledge dimensions (mental models, intuition, experience, skill) and methods of acquiring knowledge dimensions (training, job rotation, work teams) and the measurement and analysis of the link and the kind of impact between the methods of acquiring knowledge and tacit knowledge of the Angels nursing in the researched hospital, and was the questionnaire primary means of collecting information adopted by the researcher that, the research sample of (90) individuals, including the Angels nursing, has been using the statistical program spss for the purpose of conducting statistical treatments, and through the diagnosis and measurement of research variables, and test the influence and differences relations among themselves, was reached to a set of conclusions was the most important, is affected by a dimension of intuition and experience a high level of after job rotation to the variable methods of acquisition, because the work of job rotation is gaining the nurse varied experiences as transmitted in the corridors of the hospital, came to work the level of high dimension skill Effect teams and the nature of collective action in facilitating and speed the acquisition of highly skilled and participation within the same team, and affects the training of high level and more on the mental models that in the training process is more than a mental model was taken to the nurse, gave the researcher a set of recommendations, most notably, to disseminate the concept of acquiring knowledge among all cadres of nursing and assimilated to acquire meaning and make it part of the culture of the organization through job rotation, and the development of training programs in quality and quantity of nursing staffs for the purpose of raising the quality and efficiency of their performance in a manner that allows subscribers to this intensive programs learn about the latest developments in the professional work.